Development of TPACK-based e-Modules for Pre-service Mathematics Teacher Using Successive Approximation Model - Priyanda, Roni; Ihsan, Iden Rainal; Herman, Tatang; Fadhelina, Nishbah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
The purpose of this research was to develop valid and practical TPACK-based e-modules for prospective mathematics teachers. The development uses the SAM model which provides a systematic and iterative approach consisting of 3 phases, i.e., preparation, iterative design, and iterative development. The research was conducted at Universitas Samudra with the development of an e-module on one of the differential equation materials, namely homogeneous differential equations. Modules are designed using flipbooks, integrating material, problem solving exercises, and ending with project students compiling instructional designs on material mathematics. The results of the assessment by the validator team (consisting of material experts, linguists and media experts) obtained 82.22% for the level of validity, with a very decent category. On the other hand, the average student response regarding the practicality of the e-module is at 87.01 in the very practical category. Thus, the e-module on TPACK-based differential equation material is feasible and practical for use by pre-service mathematics teachers at Universitas Samudra.